1997
DOI: 10.1002/(sici)1098-2795(199709)48:1<34::aid-mrd5>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar substructures of rabbit cleaving embryos: An immunocytochemical study

Abstract: The structure‐function relationships of the nucleolar substructures were studied in preimplantation rabbit embryos, where nucleologenesis is extending over the first four cell cycles and may not be synchronous in each blastomere. Immunocytochemical methods using light and electron microscopy were applied for protein and RNA localization as well as nick translation and terminal deoxynucleotidyl transferase techniques for DNA detection. DNA was gradually associated with the periphery of the compact nucleolar pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…The onset of fibrillarin expression mirrored that of tritiated uridine incorporation into the nucleolus, first appearing in sixto eight-cell stage macaque embryos (Schramm and Bavister, 1999). It was also reported that fibrillarin acts as a genome activation marker in mice (Baran et al, 1995;Cuadros-Fernandez and Esponda, 1996), rabbits (Baran et al, 1997;PintoCorreia et al, 1995), and cows (Schram and Paprocki, 2000). In the present study, transcripts of fibrillarin, nucleolin, nucleophosmin, PAF53, and UBF were detected in all blastocysts.…”
Section: Discussionsupporting
confidence: 80%
“…The onset of fibrillarin expression mirrored that of tritiated uridine incorporation into the nucleolus, first appearing in sixto eight-cell stage macaque embryos (Schramm and Bavister, 1999). It was also reported that fibrillarin acts as a genome activation marker in mice (Baran et al, 1995;Cuadros-Fernandez and Esponda, 1996), rabbits (Baran et al, 1997;PintoCorreia et al, 1995), and cows (Schram and Paprocki, 2000). In the present study, transcripts of fibrillarin, nucleolin, nucleophosmin, PAF53, and UBF were detected in all blastocysts.…”
Section: Discussionsupporting
confidence: 80%
“…In no case was fibrillarin detected in 4-or 5-cell embryos. In similar studies in mice [43,44], rabbits [45,46], and cows (unpublished results), expression of fibrillarin at the periphery of the nucleus was initially detected at the species-specific time of genome activation, coincident with expression of nucleolin [43], protein B23 [47], and RNA polymerase I [44]. Following genome activation, the fluorescent pattern progressively changed into either a continuous layer of label in the cortex (mouse [43,44]) or into branch-shaped speckles in reticulated nucleoli (rabbit [45]; cow, unpublished results).…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, fibrillarin was also localized to the perimeter of the nucleolar precursor bodies from the 6-to 8-cell through the morula stage, forming a ring that completely encapsulated these structures, before changing into a reticulated-like pattern at the blastocyst stage. Although the specific functions of fibrillarin in embryonic transcription have not been completely defined, its expression at the periphery of the nucleolar precursor body along with nucleolin, protein B23, and RNA polymerase I [43][44][45]47], which coincides with the onset of nucleolar transcription in mouse [43,44], cattle [47], and rabbit [46] embryos, suggests a role of this protein in rRNA gene transcriptional activity. Moreover, lymphocytes, which have transcriptionally inactive nucleoli, exhibit weak labeling with fibrillarin antibodies [48].…”
Section: Discussionmentioning
confidence: 99%
“…In rabbit, Baran et al (1997) identified by electron microscopy NPBs as round shape and compact structures from the 1- to 8-cell stages. At the 16-cell stage, some NPBs (called A-NPB) displayed a less compact structure associated with RNA detection but fully functional nucleoli were only detected at the morula and blastocyst stages (Baran et al 1997).…”
Section: Introductionmentioning
confidence: 99%